Regime jurídico dos portos marítimos - Lima, Cristiana Maria Melhado Araujo (2009)
The port sector, as well as other sectors of infrastructure, has suffered significant alterations in its regulation in recent years. Since 1993, with the edition of the Law nº 8.630, known as the Law of Modernization of the Ports, which profoundly modified the legal regime of installment of the services, several government measures has been edited bringing modifications to the norms of regency of the activity. So it was with edition of the Law nº 10.233/2001, that it established principles and general lines of direction for management and operation of the infrastructure of transports, created the National Agency of Waterway Transports (ANTAQ) and tacitly revoked some provisions of the Law nº 8.630/1993; and, later, with the Law nº 11.518/2007, that created the Special Secretariat of Ports (SEP), instituted as plus an instance of regulation of the sector. Recently, the Decree nº 6.620/2008 traced the politics and lines of direction for the development and the promotion of the sector, rising again new debates of the legal regime of the public ports and privative terminals of mixing use, and, in consequence, causing the emergence of new proposals, by the ANTAQ, which now are in phase of public consultation